Survival of Macrophomina phaseolina s.l. and Verticillium dahliae during solarization as affected by composts of various maturities. (October 2015) - Kanaan, H.; Medina, Sh.; Krassnovsky, A.; Raviv, M.
Abstract: Solarization is commonly used against several soilborne pathogenic fungi, and is an effective, environmental-friendly substitute for chemical control or soil steaming. This study aimed to verify solarization effectiveness as a control measure against the pathogens Macrophomina phaseolina s.l. ( sensu lato ) ( MP ) and Verticillium dahliae ( VD ) when combined with compost of various maturity levels. This assumes that immature compost can help to eradicate the pathogens as its degradation can raise the temperature below the tarp. The survival rates per gram of MP and VD were tested at depths of 10 and 20 cm. At both depths in the solarized treatments, VD was eradicated during the first 2 weeks, whereas in the non-solarized treatments the level of VD incidence decreased but not to total elimination. Four weeks after the beginning of the experiment, about 5000 colony forming units (CFUs) of VD survived in the non-solarized treatment. MP survived the solarization process. The presence of compost of any maturity level did not contribute to a temperature increase in the solarized part during the day. At night, in the non-solarized treatments, the average minimal temperature rose by almost 1.4 °C in the immature-compost-treated soil. Solarization at a maximal temperature of almost 48 °C, as found in the field experiment, could eradicate VD, but this temperature was not sufficiently high to eradicate MP . We also aimed to determine the minimal threshold temperature for eradication of MP . For this we used an incubator with cycling temperatures, to simulate the daily cycles of soil temperature during solarization. MP survived a maximal temperature of 52 °C during a 4-week laboratory experiment with cycling temperatures; it was totally eliminated after 4 weeks at a maximal temperature of 54 °C and after 2 days at a maximal temperature of 56 °C. Highlights: Solarization conducted under Mediterranean conditions could eradicate Verticillium dahliae, but not Macrophomina phaseolina. Compost in three maturation levels did not raise the temperature under solarization condition. Exposing MP to various temperatures for 4 weeks caused eradication at 54 °C, above soil solarization temperature.